Hippocampal volume and cell proliferation after acute and chronic clozapine or haloperidol treatment - Schmitt, Andrea; Weber, S.; Jatzko, Alexander; Braus, Dieter F.; Henn, Fritz A. (Journal of neural transmission, 2004)
Summary.The dentate gyrus contains progenitor cells possessing the capacity to proliferate until and throughout adulthood. There is little information about the influence of antipsychotics on cell proliferation. To address this, we investigated the influence of acute and chronic haloperidol and clozapine treatment on the total number of newly dividing cells and hippocampal volume using an animal model with doses equivalent to the therapeutic range in humans.Rats were treated with either acute or 28 days haloperidol (1 mg/kg i.p. or 1,5 mg/kg/day oral) or clozapine (30 mg/kg i.p. or 45 mg/kg/day oral). After BrdU injection, immunohistochemistry was performed in serial hippocampal brain sections. Total BrdU-labeled cell number and hippocampus volume were estimated using stereological methods. Neither neuroleptic altered total number of newly dividing cells in the dentate gyrus. In contrast, chronic haloperidol treatment did increase total hippocampal volume suggesting that haloperidol alters neuroplastic processes or glial morphology rather than cell proliferation.
Published: 03 December 2003
Gesehen am 03.11.2020